POLIMORPHIC CHARACTERIZATION OF ESR1 AND FOXL2 GENES AND THE ASSOCIATION OF THEIR INTERACTION WITH PRODUCTIVE TRAITS OF BROWN LOCAL IRAQI CHICKENS - Abu-Rekaiba, R. I. A.; AL-Anbari, E. H.; Razuki, W. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The estrogen receptor 1(ESR1) and fork-head box L2 (FOX L2) genes play a pivotal role in regulation of egg formation in poultry. this study aimed to investigate interaction between ESR1 and FOXL2 in the productive performance of brown local Iraqi chickens (BLIC). A total of 104 BLIC represented from the F4th generation of local chicken selected for high egg productions were used. Two novel single nucleotide polymorphism (SNPs), one of them in ESR1 (T57198C) intron 3, and another of FOX L2 (C919T) gene within encoding region were identified through PCR-DNA sequencing. Six haplotypes (H1=TTCC, H2=TTCT, H3=TCCC, H4=TCCT, H5=CCCC, H6=CCCT) were obtained due to interaction between these two SNPs. Chi-square analysis showed no significant  in genotypic and allelic frequencies for each SNP which revealed that both genes were agreement with Hardy-Weinberg equilibrium. Association analysis of haplotypes with production traits revealed that individuals have H4 genotype achieved higher body weight at sexual maturity, at 60 weeks of age and egg weight at 45 and 60 weeks of age, whereas, the higher number of eggs were exhibited in individual with H6 from onset egg till 60 weeks of age. The two haplotypes; H4(TCCT) and H6(CCCT) showed better combination than others with respect to production performance. In conclusion, our findings provided new evidence that the two genes (ESR1 and FOXLl2) with special interaction may have potential effects on productive traits of chickens and beneficial effects in laying breeding programs.